Evaluation of Solar Energy Efficiency by Composite Index over Four Continents - Haine Kamel (Sciendo, 2021)
This paper aims to provide an evaluation of solar energy efficiency by composite index and to compare the value of solar energy across 19 countries located over four continents: Europe, Africa, America, and Asia. 15 indicators were evaluated for the year of 2019 and grouped into four dimensions: economic, social, technical, and environmental. Analytical Hierarchy Process (AHP) was used to estimate the weight of each indicator, and consistency tests were calculated to evaluate weight efficiency. The obtained results of the SEI reveals that the technical dimension and economic dimension play an important role in the solar energy efficiency of a country. The results indicate potential improvement areas for increasing solar efficiency. SEI can be used as a tool in assessing solar energy potential integration in a country.